STRENGTHENING GREEN ACCOUNTING LITERACY FOR THE INDONESIAN MIGRANT WORKERS ASSOCIATION IN PETALING JAYA, SELANGOR, MALAYSIA TO PROMOTE SUSTAINABLE WORK PRACTICES - Basrowi Basrowi; Juhari Ali; Rahemee Rahemee; Mohd Mizan bin Asalam; Bambang Dwi Suseno; Gema Ika Sari; Nani Rohaeni; Riani Puasarin; Hidayatullah Hidayatullah; Nining Sulastri Kurnia; Fitriyansyah Fitriyansyah (International Journal of Engagement and Empowerment (IJE2), 2026)
This community service program aimed to strengthen green accounting literacy among members of the Indonesian Migrant Workers Association in Petaling Jaya, Selangor, Malaysia, in order to promote sustainable work practices and improve financial accountability. The program was designed to address the limited understanding of environmentally oriented accounting practices among migrant workers, particularly in relation to financial management, resource efficiency, and sustainable economic behavior. The implementation method consisted of training sessions, mentoring activities, interactive discussions, and practical simulations related to green accounting principles, simple financial recording, budgeting, and sustainable workplace practices. Participants were introduced to the importance of integrating environmental awareness into financial decision-making and daily economic activities. The results of the program indicate significant improvements in participants’ understanding and application of green accounting concepts. First, the program successfully strengthened participants’ awareness of sustainable financial governance, reflected in better budgeting practices, improved financial discipline, and increased understanding of environmentally responsible economic behavior. Second, participants demonstrated improved ability to implement accounting-based practices through systematic transaction recording and the preparation of simple financial reports that considered resource efficiency and sustainability aspects. Third, the program contributed to the enhancement of participants’ work competitiveness and adaptability by encouraging the use of financial information for planning, cost control, and sustainable decision-making. Overall, the program proved effective in increasing green accounting literacy and fostering sustainable work practices among Indonesian migrant workers in Malaysia.